Clinical characteristics of challenging catheter ablation procedures in patients with WPW syndrome: A 10 year single-center experience. Issue 4 (October 2020) - Fujino, Tadashi; De Ruvo, Ermengildo; Grieco, Domenico; Scará, Antonio; Borrelli, Alessio; De Luca, Lucia; Panuccio, Marco; Fagagnini, Alessandro; Bruni, Giuseppe; Sciarra, Luigi; Calò, Leonardo
Highlights: After the first procedure, 92.4% of the WPW patients were cured by ablation. In half of recurred patients, accessory pathway (AP) recurrences were recorded within 36 h after ablation. Parahisian and multiple APs were significant independent predictors of AP recurrences after the 1st procedure. Abstract: Background: Catheter ablation is the established treatment for patients with symptomatic Wolff–Parkinson–White syndrome (WPW). However, some patients undergo a challenging ablation or have recurrences during the early post-ablation phase. The aim of this study was to evaluate the clinical factors associated with an unsuccessful ablation outcome or repeated sessions. Methods: Four hundred seventy-five symptomatic consecutive WPW patients (38.2 ± 16.2 years old, 61% men, 69% with pre-excitation) who underwent an accessory pathway (AP) ablation from August 2005 to December 2015 were enrolled. When APs recurred, a redo ablation procedure was performed according to the patients' desire. Results: Four hundred thirty-nine patients (92.4%) were cured by ablation, but it failed in 36 (7.6%) after the first procedure. Seventeen patients had AP recurrences during the acute phase within 36 h post-ablation. On the other hand, 4 were identified after more than one year. In a multivariate logistic regression analysis, multiple, parahisian, and broad APs were significant independent predictors of recurrences after the 1st procedure, with odds ratios of 14.88 ( p  < 0.001), 10.14 ( p  < 0.001), and 6.88 ( p  < 0.001), respectively. Finally, 468 patients (98.5%) received a successful ablation during a mean follow-up of 8.3 ± 3.0 years. However, after the final procedure no significant predictors were recognized. Out of 508 total procedures, three major (0.6%) complications occurred. Conclusions: Symptomatic WPW patients with multiple, parahisian, and broad APs had a significantly higher risk of recurrence. In half of the recurrence patients, AP recurrences were confirmed during the acute phase, but were rarely recorded in the very late phase.